Tarea de toma de signos vitales básicos con robot humanoide (2020)
This document details the capstone project for Computer Science and Engineering, which consists of the development of a computational prototype that allows the robot Pepper from Softbank Robotics to carry out the task of performing rounds in a hospital ward collecting the vital signs of patients who are institutionalized in wings of low complexity pathologies for multiple medical and surgical specialties by means of an attachment prototype designed for the Mechanical Engineering part of this capstone project. As this is a joint project between the two departments, the corresponding documents share content between sections. The computational prototype consists of two parts, a complete development that includes the human-robot interaction and path planning, and a simulation of the planning and execution of these routes. The first one was developed in Android Studio using Java and the framework NAOqi from Softbank Robotics and its validation was carried out through the Android Studio...